SCHOOL IN USE AND DEVELOPMENT OF ICT-BASED LEARNING MEDIA AT PLUMBANGAN 01 STATE ELEMENTARY SCHOOL - Suwarno; Isna Nurul Inayati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
The results of the analysis of the 8 SNP standards contained in the School Self Evaluation (EDS) UPT SD Negeri Plummbang 01 researchers found weaknesses in process standards, especially teacher competence, which still needed to be improved in the process of using ICT-based learning media and development. The type of this research is school action research. This research was conducted at Plukangan 01 Public Elementary School in November 2021 with the research subjects being all teachers of Resapombo Public Elementary School. The technique of collecting data from this school action research is through qualitative data obtained from observation/observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Based on the results of reflection, monitoring and evaluation that have been carried out, it can be concluded that cycle 1 and cycle 2 activities have increased so that all objectives of the school action research activities are declared successful. Teacher competence in using ICT-based learning media and development is said to have increased.